METHODOLOGY OF SWIMMING LESSONS FOR PRESCHOOLERS (Proceedings of International Educators Conference, 2023)
The purpose of the study: to develop a methodology and program for mastering with water and teaching swimming, adequate to the age characteristics of preschoolers. The contingent of the subjects: children 4-7 years old, a total of 564 people. On the basis of the experimental data obtained, a methodology was developed for teaching the technique of sports swimming to children 4-7 years old, which helps to reduce the time for mastering with water and to study the methods of crawl swimming on the chest and on the back in all age groups. The expedient sequence of application of exercises is substantiated.